The identity politics in Indonesian football during the colonial period - Indhar Wahyu Wira Harjo (Journal Sport Area, 2022)
This research objective is to examine social stratification in the football sector in Indonesia during the colonial period. Social stratification is the beginning of the occurrence of discriminatory treatment differences. This research applies a qualitative research method with a literature study approach. The data sources in this research are obtained from journal articles, books, and mass media relevant to social stratification in the football sector during the colonial period. The selection of information sources used internal and external criticism to sort out the information collected through document study techniques. The data collected is then processed using interactive data analysis techniques to obtain answers to research problems. The research results show that social stratification took place individually and communally. Local football players are in the lowest position, as are football clubs and football federations formed by local communities. The system established by the colonial government placed European and Chinese football players into a higher layer than local players. This distinction triggered discriminatory treatment against local players to reduce the opportunity for football players and clubs to access the field and competitions organized by the federation formed by the Dutch colonial government. This condition, on the one hand, shows the process of imitating the local community towards sports brought by the colonizers. On the other hand, the imitation also contains resistance to discriminatory treatment as well as colonial practices. Changes in such discriminatory conditions are needed so that similar practices do not occur in other life aspects.